Perception of Management Personnel on the Introduction of Home Office System in Their Organisations - Rethinam, Guna Seelan (1999)

(untitled)
Drastic development in the telecommunication and computer technology has encouraged the computerisation of private and public sectors in Malaysia. Advancement of this new information technology provides new opportunities for Malaysians and encourages the government to build an information-rich society by the year 2020. In vision 2020 development of home environment computer networking will be emphasised. This study was conducted to determine the perception of top managerial personnel on home office system. A total of 78 management personnel from organisations listed in KLSE participated in this study. Data were collected through structured mail questionnaire and analysed using SPSS ver. 7.5 (W). The findings showed that management personnel were highly favourable towards adopting home office system. The study found a negative and weak relationship between perception and perceivable barriers. The assumption is that there is a basic demand and eagerness among the organisational practitioners in adopting home office system in their organisation. However the management need to be willing to exert considerable effort in introducing the system in their organisations. The present situation in their respective organisations strongly indicative that, utilisation of information technology is fundamental for employees' personal development and job satisfaction. This study concluded that home office system improve their employees job satisfaction and personal development. Therefore the management personnel should develop a policy to build a productive virtual workforce with the consideration of the existing perceivable barriers in order to be successful in introducing the system in their organisations.